HUBUNGAN ANTARA KETERTARIKAN MAHASISWA DENGAN LAGU TERHADAP KEMAMPUAN BERBICARA BAHASA INGGRIS - Megawati Megawati; Dini Fitriani; Neng Nurwiatin; Ivon Mukaddamah (Jurnal Inovasi Penelitian, 2022)
This study aims to know the relation between students’interest song on their speaking skill. There are some problems such as what are the interest students in song has relation with their speaking skill. This study was conducted to the first semester students at STKIP Kusumanegara Jakarta. Reasearch of the method is quantitative with twenty students as the sample. Data was collected by speaking test, questionnaire which has relation students’interest in song. This study use two variable. Independent variable is students’interest in song and dependent variable is speaking skill. The result from this study, it was gotten sig. (2.tailed) 0.014 < 0.05, it means high score in speaking skill influenced by students’interest in song. There is positive relation between students’interest in song on their speaking skill. Coefficient correlation 0.539 > 0.05, it means if students’interest is high so speaking skill is high and if students’interest in song is low so their speaking skill is low.